Research of ZCZ ternary sequence pairs set based on pseudorandom sequence - LI Zhao-bin1; JIANG Ting1; ZHOU Zheng1 (Tongxin xuebao)
Pseudorandom sequence was used in zero correlation zone（ZCZ） sequence pairs, and then a new construction method for ZCZ ternary sequence pairs set was presented. The general construction method of ZCZ sequence set was based on perfect sequence, but the new construction method was based on pseudorandom sequence and orthogonal matrix. ZCZ ternary sequence pairs set with certain length, family size and zero correlation zone could be synthesized through interleaved transformation when suitable shift sequences were selected. The capacity of ZCZ ternary sequence pairs set constructed by the proposed method is so large that it can satisfy requirements of engineering applications.